SIBLING RELATIONSHIP DURING MIDDLE ADULTHOOD IN RELATION TO FAMILY ENVIRONMENT - SHOURYA NEGI* and SHANTI BALDA, (The Journal of Research ANGRAU, 2020)
The study was conducted in the year 2019 with adults aged between 40 to 50 years old in Uttarakhandand Haryana states. The total sample was composed of 240 adults, 120 from Haryana and 120 from Uttarakhand(60 males and 60 females from both the states). It was recorded that 63.3% respondents from Uttarakhandand 68.3% respondents from Haryana perceived average level of overall family environment. Respondents withhigh level of family environment had more contact with their siblings (Mean=26.72), experienced more emotionalcloseness (Mean=25.96) and less conflict (Mean=24.38) with their siblings, and also confided more (Mean=16.45)with their siblings in comparison to the respondents with low and average family environment. Overall, siblingrelationship was better when family environment was better. Regression analysis unveiled family environmentas a predictor and accounted for 6.7 percent variance in sibling relationships, F (1,239) = 18.24, P